Structure of prodigiosin from Serratia marcescens NJZT-1 and its cytotoxicity on TSC2-null cells - ZHAO,Yinjuan (2021)
Abstract Prodigiosin, a secondary metabolite extracted from Serratia marcescens (S. marcescens), could induce apoptosis in various cancer cells, with however low toxicity on normal cells. The red pigment was extracted from a strain S. marcescens NJZT-1 isolated from soil, which had antibacterial activity. Spectral analyses (LC-ESI-MS, UV-VIS spectrophotometry, infrared spectra and HPLC) and TLC indicated the presence of prodigiosin in the extracellular bacterial culture extracts. The red pigment effectively killed the TSC2-null cells, whose mutation resulted in the progressive and systemic disease LAM. Our findings provide interesting evidence and important basis for the development of new therapeutic compounds with high potential effects against TSC2-null cells.